Protecting and Expanding Railway Networks to Hedge against Disruptions: A Model with Travel Segments. (6th June 2022) - Starita, Stefano; Irawan, Chandra Ade; Jindahra, Pavitra
Abstract : Railway systems are instrumental to countries' economies. They are also vulnerable to man-made and natural disruptions and therefore need to be protected. This paper introduces an optimization model to identify the set of fortifications and network expansions to mitigate the impact of worst-case disruptions. The model incorporates multiple travel segments allowing to study the impact of different route choice behaviours. A Benders decomposition approach is developed to solve the bilevel problem alongside a more efficient nested GRASP heuristic. The algorithms are tested and compared on a set of artificial grids. A case study is developed using the Central London Tube network to provide managerial insights.